Why victims of undermining at work become perpetrators of undermining: An integrative model - LEE, Ki Young (Institutional Knowledge at Singapore Management University, 2016)
We develop and test an integrative model explaining why victims of workplace social undermining become perpetrators of undermining. Conceptualizing social undermining as a norm-violating and a resource-depleting experience, we theorize that undermining victimization lowers interpersonal justice perceptions and depletes self-regulatory resources, and these 2 mechanisms in tandem trigger a moral disengagement process that influences subsequent undermining behaviors. We further theorize that moral identity functions as a boundary condition: high moral identity attenuates whether interpersonal injustice and resource depletion shape moral disengagement and whether moral disengagement translates to subsequent undermining. A field study of bank employees provides empirical support for the mediating mechanisms, and shows that employees who have high moral identity are less likely to respond to interpersonal injustice by morally disengaging and to translate moral disengagement to undermining.